Incidence de la technique d’irrigation sur la pénétration en profondeur de la solution d’irrigation dans les tubules dentinaires – Étude in vitro - EL-HADDAD, Nadine (International Arab Journal of Dentistry (IAJD), 2010)
The irrigation of the endodontic system depends on two factors : the irrigant and the method of irrigation. Sodium Hypochlorite remains the irrigant of choice of the endodotist. Its ultrasonic activation has proven to improve its cleaning ability on the walls. Its effect on bacteria inside dentinal tubules still needs to be investigated. To measure the degree of penetration inside the tubules, the use of a dye marker with static and dynamic methods is compared.